Functional Identification of EjGIF1 in Arabidopsis and Preliminary Analysis of Its Regulatory Mechanisms in the Formation of Triploid Loquat Leaf Heterosis - Liu, Chao; Huang, Renwei; Wang, Lingli; Liang, Guolu (Frontiers in Plant Science, 2021)
Although several results have been obtained in triploid loquat heterosis (i.e., leaf size of triploid loquat) studies in the past years, the underlying mechanisms of the heterosis are still largely unknown, especially the regulation effects of one specific gene on the corresponding morphology heterosis. In this study, we sought to further illustrate the regulatory mechanisms of one specific gene on the leaf size heterosis of triploid loquats. A leaf size development-related gene (EjGIF1) and its promoter were successfully cloned. Ectopic expression of EjGIF1 in Arabidopsis showed that the leaf size of transgenic plantlets was larger than WTs, and the transgenic plantlets had more leaves than WTs. QRT-PCR showed that the expression level of EjGIF1 showed an AHP expression pattern in most of the hybrids, and this was consistent with our previous phenotype observation. Structure analysis of EjGIF1 promoter showed that there were significantly more light-responsive elements than other elements. To further ascertain the regulatory mechanisms of EjGIF1 on triploid loquat heterosis, the methylation levels of EjGIF1 promoter in different ploidy loquats were analyzed by using bisulfite sequencing. Surprisingly, the total methylation levels of EjGIF1 promoter in triploid showed a decreasing trend compared with MPV, and this was also consistent with the qRT-PCR results of EjGIF1. Taken together, our results suggest that in addition to promoting leaf size development, EjGIF1 could also promote leaf primordium formation, and demethylation of EjGIF1 promoter in triploid loquats leads EjGIF1 exhibits over-dominance expression pattern and then further promotes leaf heterosis formation.